Lysophosphatidic Acid–Induced EGFR Transactivation Promotes Gastric Cancer Cell DNA Replication by Stabilizing Geminin in the S Phase - Zhao, Haile; Gezi, Gezi; Tian, Xiaoxia; Jia, Peijun; Morigen, Morigen; Fan, Lifei (Frontiers in Pharmacology, 2021)
Geminin, an inhibitor of the DNA replication licensing factor chromatin licensing and DNA replication factor (Cdt) 1, is essential for the maintenance of genomic integrity. As a multifunctional protein, geminin is also involved in tumor progression but the molecular details are largely unknown. Here we found that lysophosphatidic acid (LPA)-induced up-regulation of geminin was specific to gastric cancer cells. LPA acted via LPA receptor (LPAR) 3 and matrix metalloproteinases (MMPs) signaling to transactivate epidermal growth factor receptor (EGFR) (Y1173) and thereby stabilize geminin expression level during S phase. LPA also induced the expression of deubiquitinating protein (DUB) 3, which prevented geminin degradation. These results reveal a novel mechanism underlying gastric cancer progression that involves the regulation of geminin stability by LPA-induced EGFR transactivation, and provide potential targets for signaling pathway- and tumor cell-specific inhibitors.